Requirements for court rulings in the light of guarantees of the right to a fair trial - L. A. Terekhova; A. V. Ryabusova (Правоприменение, 2024)
The subject of the study. The legislator does not establish a list of requirements that the rulings of the court of first instance must meet. The article analyzes the requirements for the rulings of the court of first instance in civil proceedings, in comparison with the requirements for court decisions based on domestic procedural legislation and scientific literature. The purpose of the article is to confirm that the main requirements for court rulings are legality, validity, motivation, and enforceability.The research methodology includes the formal-logical method, analysis, synthesis, logicallegal method.Main results. An analysis of domestic legislation and scientific literature led to the conclusion that, based on the requirements that court rulings must meet, the legislator has not correctly defined a list of definitions that must be substantiated, motivated and subject to appeal separately from the final judicial act. The category of protocol definitions should be rather exclusive. Such determinations must be made if it is not required to state the motives for the decision and if it does not affect the essence of the final judicial act.Conclusions. Court rulings must meet the above requirements by analogy with court decisions. The issues raised in this article have not only theoretical, but also practical meaning in relation to civil procedural law in the Russian Federation. The practical problem is that at the moment the legislator has not correctly defined the list of definitions that must be substantiated, motivated and subject to appeal separately from the final judicial act. Court rulings in civil proceedings subject to appeal must meet the requirements of legality, validity, motivation, and enforceability. Contrary to this, in practice the opposite situation often occurs. The category of protocol definitions should be rather exclusive. Such determinations must be made if it is not required to state the motives for the decision and if it does not affect the essence of the final judicial act. Otherwise, this will lead to a violation of the fundamental right to a fair trial and a restriction of a person's access to justice.